On the massive disks in low surface brightness galaxies - Saburova, A.S. (Advances in Astronomy and Space Physics, 2011)
On the example of four low surface brightness galaxies we demonstrate that the mass-to-light ratio of their disks may be found from the condition of marginal gravitational stability. In this case their surface densities and halo/disk mass ratios appear to be rather typical for normal galaxies, and this does not conflict with their rotation curves.